SUBEPIDURAL HEMATOMA IN STROKE: A RARE BUT CRITICAL CONSIDERATION IN ADULT PATIENTS - Ibragimov Sardorbek Tolib o’g’li; Shokirova Mehruza Komiljon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Subepidural hematoma (SEH) is an uncommon yet potentially life- threatening condition that can arise in the context of cerebrovascular events, including ischemic and hemorrhagic strokes. Unlike epidural and subdural hematomas, SEH occurs in the dural border zone, presenting unique diagnostic and management challenges. This article explores the pathophysiology, clinical manifestations, neuroimaging characteristics, and therapeutic approaches for SEH in stroke patients, emphasizing its role in secondary neurological deterioration. Given the limited literature on this topic, we highlight key case reports, propose diagnostic algorithms, and discuss potential surgical and conservative treatment strategies.